PENGARUH PEMBERIAN SERBUK PINANG TERHADAP PERFORMA DAN INDEKS PEFORMANS (IP) BROILER - Nilawati Nilawati; A Gustian (Wahana Peternakan, 2023)
The purpose of this study was to identify the effect of areca nut powder on broiler performance and performance index (IP). The study was conducted on 200 DOC broiler reared up to 28 days old. This study used a completely randomized design with 4 treatments and 5 replications. The treatment given was the addition of areca nut powder in the broiler ration. The treatment given consisted of control, addition of 1.5%, 3% and 4.5% areca nut powder. Variables in this study included feed consumption, body weight gain, final weight, feed conversion, and performance index (IP). The results of this study indicated that the administration of areca nut powder at a level of 1,5%, 3% and 4.5% did not show a significant difference (p> 0.05) to performance and performance index (IP) of broilers. The results of this study found that the administration of areca nut powder at a level of 1,5% showed better results than the control, 3% level and 4.5% level of areca nut powder. Keywords : Areca Nut Powder, Broiler, Broiler Performance, and Performance Index (IP).